Te Ha Whakawairua, Whakatinana i te Mātauranga Māori i Te Whare Wānanga: The validation of Indigenous knowldge within the university academy - Ka’ai, Tania (Te Kaharoa, 2008)
This article employs a case-study approach to examine the crucial roles played by Māori Studies Departments in Universities throughout Aotearoa/New Zealand. Comparisons are drawn with similar centres of learning, teaching, and research in among other indigenous groups, and the article reveals the crucial role these departments play.